Opportunities and Challenges of Common European Framework of Reference for Language (CEFR) Standardization in Arabic Language Learning - Pratama, Arya Wahyu; Mahliatussikhah, Hanik; Murtadho, Nurul; Kholisin, Kholisin (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2024)
Islamic boarding schools should adapt the learning curriculum to the needs of current developments. Among them is preparing students to communicate in an international language, namely Arabic, especially in the era of industrial revolution 4.0. Unfortunately, Arabic language learning in Islamic boarding schools often still uses classical methods. Even though the use of Arabic as a communication language is really needed by students in the future. This research tries to reveal the opportunities and challenges of learning Arabic within the Common European Framework of Reference for Language (CEFR) framework in Islamic boarding schools. The researcher chose the An-Nur 2 Al-Murtadlo Malang Islamic Boarding School, which provides Arabic language learning to its students. This qualitative descriptive research was carried out by means of interviews and observations with caregivers, ustadz (teacher), and students to determine the extent of their understanding of CEFR. As a result, the Islamic boarding school did not implement the CEFR curriculum because they were not familiar with it. Among the opportunities for implementing the CEFR curriculum in Arabic language learning at Islamic boarding schools are improving the quality of learning and learning accessibility, while the challenges faced are curriculum adjustments and limited human resources.